ABOUT PSYCHOLOGICAL VARIABLES IN APPLICATION SCORING MODELS - PABLO ROGERS (RAE - Revista de Administração de Empresas, 2015)
The purpose of this study is to investigate the contribution of psychological variables and scalessuggested by Economic Psychology in predicting individuals’ default. Therefore, a sample of 555individuals completed a self-completion questionnaire, which was composed of psychologicalvariables and scales. By adopting the methodology of the logistic regression, the followingpsychological and behavioral characteristics were found associated with the group of individuals indefault: a) negative dimensions related to money (suffering, inequality and conflict); b) high scoreson the self-efficacy scale, probably indicating a greater degree of optimism and over-confidence; c)buyers classified as compulsive; d) individuals who consider it necessary to give gifts to children andfriends on special dates, even though many people consider this a luxury; e) problems of self-controlidentified by individuals who drink an average of more than four glasses of alcoholic beverage a day.